Business cycle synchronization of the euro area with the new and negotiating member countries - Osborn, Denise R.; Neanidis, Kyriakos C.; Savva, Christos S. (My University, 2010)
We examine business cycle synchronizations between the euro area and the recently acceded EU and currently negotiating countries. Strong evidence is uncovered of time-variation in the degree of co-movement between the cyclical components of monthly industrial production indicators for each of these countries with a euro area aggregate, which is modelled through a bivariate VAR-GARCH specification with a smoothly time-varying correlation that allows for structural change. Where required to account for the observed time-variation in correlations, a double smooth transition conditional correlation model is used to capture a second structural change event. After allowing for dynamics, we find that all new EU members and negotiating countries have at least doubled their business cycle synchronization with the euro area or changed from negative to positive correlations, since the early 1990s. Furthermore, some have exhibited U-curved or hump-shaped business cycle correlation patterns. The results point to great variety in timing and speed of the correlation shifts across the country sample. Copyright 2009 John Wiley & Sons, Ltd.
Keywords: Business cycle; Conditional correlations; Synchronization; Volatility